1990
DOI: 10.1128/jcm.28.5.894-897.1990
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal DNA, iron-transport systems, outer membrane proteins, and enterotoxin (heat labile) production in Salmonella typhi strains

Abstract: We examined a representative collection of Salmonella typhi strains from Chile, Peru, Mexico, India, and England for the presence of several properties. Ail strains had a conserved pattern of outer membrane proteins, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The electrophoresis profiles of chromosomal DNA digested with EcoRI and PstI restriction enzymes were similar for all the strains. A conserved pattern of hybridization was observed when digested chromosomal DNA was hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Comment. In previous studies we and other investigators have found that S. typhi strains from different geographic areas are virtually identical, compatible with the concept that S. typhi strains are clonal in origin (4,17,20,23,25). Faundez et al (4) found minimal differences among strains from Chile, Peru, Mexico, India, and England by using chromosomal restriction digests, Southern blot analysis (with probes to the 36-kDa porin, enterobactin synthesis, and enterobactin receptor genes), and outer membrane protein profiles.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Comment. In previous studies we and other investigators have found that S. typhi strains from different geographic areas are virtually identical, compatible with the concept that S. typhi strains are clonal in origin (4,17,20,23,25). Faundez et al (4) found minimal differences among strains from Chile, Peru, Mexico, India, and England by using chromosomal restriction digests, Southern blot analysis (with probes to the 36-kDa porin, enterobactin synthesis, and enterobactin receptor genes), and outer membrane protein profiles.…”
supporting
confidence: 91%
“…While it is reasonable to hypothesize that variations in clinical presentation are related to strain differences, previous studies have suggested that with few exceptions S. typhi represents a single clone that has shown minimal intraspecies divergence in its spread to different parts of the world (4,17,20,23,25). The present study was designed to look more closely at this issue by using strains from Peru (an area with relatively mild disease) and Indonesia (an area in which disease manifestations may be quite severe).…”
mentioning
confidence: 99%
“…Iron is an essential nutrient for both eukaryotic and prokaryotic cells and plays a central role in electron transport chains involved in intermediary metabolism [1,2]. Because its reactivity under aerobic conditions can generate toxic free radicals, strict control of iron uptake and localization is a necessity.…”
Section: Introductionmentioning
confidence: 99%
“…Because its reactivity under aerobic conditions can generate toxic free radicals, strict control of iron uptake and localization is a necessity. Within mammals for example, levels of free iron are estimated to be less than 10 315 mM because intracellular iron is complexed with heme, Fe^S proteins and ferritin, and extracellular iron is complexed with transferrin in the plasma or with lactoferrin at mucosal surfaces and in exocrine secretions [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation